The seafloor heat flux driven by bottom water temperature variation in the Yellow and Bohai Seas. (September 2022) - Yang, Guang-Bing; Xia, Changshui; Xiong, Xue-Jun; Feng, Zhi-Tao; Chen, Zhao; Yang, Yang; Ma, De-Jing; Ju, Xia; Zheng, Quanan; Yuan, Yeli
Abstract: The Yellow and Bohai Seas (YBS) are shallow marginal seas located at the temperate latitudes of the western North Pacific. The seasonal bottom water temperature variation in the YBS can be greater than 20 °C and therefore generates significant seafloor heat flux, which significantly changes both the sediment temperature profile and heat content of the overlying water column. In this study, we investigated the seafloor heat flux driven by bottom water temperature variation in the YBS using a high-resolution numerical ocean model and a one-dimensional sediment temperature model. The results showed that seafloor heat flux in the area shallower than 50 m was on the order of 10 W/m 2 . The seafloor heat flux was larger than the lateral heat flux driven by circulation and ranked second only to surface net heat flux accounting for the most important forcing mechanism of ocean heat content variation in the coastal YBS. The accumulated seafloor heat flux during the sediment cooling/warming season could warm/cool the overlying water column by about 1 °C in the coastal YBS where the depth is shallower than 30 m. The depth of sediment affected by seafloor heat flux (seasonal sediment temperature variation >0.1 °C) could be as deep as 10 m. The complex spatial–temporal distribution of seafloor heat flux generated a complex distribution of sediment temperature and sound speed, which may have an important effect on acoustic wave propagation in the YBS. Highlights: Bottom water temperature variation generates significant seafloor heat flux. Seafloor heat flux is on the order of 10 W/m 2 in the coastal Yellow and Bohai Seas. Seafloor heat flux affects ocean heat content significantly. Seafloor heat flux generates complex sediment sound speed distribution.